Between Frailty and Institutional Reform. The Case of Romania - Flavian Clipa; Raluca Irina Clipa (CES Working Papers, 2014)
Our approach aims to emphasize the role that the institutional legacy of the past has in generating institutional blockages in transition countries (including Romania), while advancing several courses of action in order to overcome the difficulties found in the socio-economic frameworks. We believe that the success of the transition to capitalism equals most often with a institutional reconfiguration supported by the participation and active involvement of civil society.
Keywords: E02; K4; 330; institution; performance; legal system